Research on a laddered chape from a Late La Tène scabbard with an openwork fitment from the River Ljubljanica - Istenič, Janka; Kosec, Ladislav; Perovšek, Sonja; Gosar, Mateja; Nagode, Aleš (Arheološki vestnik, 2011)
The paper gives the results of our research into the technique of manufacture of the laddered chape from the sword scabbard with openwork fitment from the River Ljubljanica. In addition to characterisation of the alloys by proton-induced X-ray emission spectrometry (PIXE; cf. Šmit, Istenič, Perovšek 2010) the study included observation of fragments of bridges from the laddered chape using scanning electron microscopy (SEM), semi-quantitative chemical analysis of minute areas under an electron microscope (SEM/EDS) and metallographic research. Results of the study indicate that the laddered chape was made of forged steel and that the very thin layers (lamellae) of bronze in the front bridges acted as solders, thus giving an idea of how the laddered chape was constructed.